Atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase and preparation method of atomized magnesium-based hydrogen storage composite material
By introducing rare earth titanium complex phase into magnesium-based hydrogen storage materials, using atomization method and mechanical dry ball milling technology to form a nano-scale particle structure, solving the problems of high hydrogen absorption and slow reaction rate in magnesium-based hydrogen storage technology , realizes rapid hydrogen exchange and efficient hydrogen storage under room temperature conditions, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411380190.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Magnesium-based solid hydrogen storage technology has problems such as high hydrogen absorption and discharge temperature and slow reaction rate, which leads to challenges in its application. The existing catalyst improvement effect is limited and costly. Preparation methods such as mechanical crushing have environmental pollution and safety risks.
Atomized magnesium-based hydrogen storage composite material containing rare earth titanium composite phase is prepared by atomization method to mix magnesium-based hydrogen storage alloy with rare earth titanium composite phase, and the mechanical dry method is used to uniformly form a nano-scale particle structure to reduce hydrogen absorption and discharge Temperature and increase reaction rate.
It realizes rapid absorption and discharge of hydrogen under near room temperature, significantly reducing activation energy consumption and time, improving hydrogen storage efficiency and kinetic performance, and the preparation process is simple and efficient, suitable for large-scale production.
Smart Images

Figure CN119265462A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase and a preparation method thereof, belonging to the technical field of hydrogen storage materials and hydrogen storage applications. Background Art
[0002] Hydrogen energy has the characteristics of abundant resources, carbon-free, high energy density (120MJ / kg), and diverse application scenarios. It has great application potential in reducing environmental pollution and promoting energy transformation, so it has become a global development strategy and competition focus. At present, safe and efficient hydrogen storage and transportation technology is one of the main bottlenecks restricting the development of the hydrogen energy industry chain. Compared with traditional hydrogen storage technology, solid-state hydrogen storage technology based on magnesium-based materials has the advantages of low cost, high hydrogen storage density (7.6wt.% and 110g H / L), safety, high efficiency and good reversibility, which opens up greater possibilities for the large-scale utilization of hydrogen energy. However, the inherent thermodynamic and kinetic challenges of magnesium-based hydrogen storage still exist, which directly leads to its shortcomings of high hydrogen absorption and desorption temperature (>350℃) and slow reaction rate. Therefore, solving these problems is still the main scientific challenge for the widespread application of magnesium-based solid-state hydrogen storage technology. In recent decades, magnesium has made great progress as a hydrogen storage material. Researchers have adjusted the different kinetic and thermodynamic properties of magnesium-based materials through alloying, catalyst doping, nano-sizing and nano-confinement.
[0003] Alloying is one of the simplest and most efficient ways to improve the hydrogen storage performance of magnesium-based materials, and is most conducive to achieving the goal of industrialization. Reilly Jr (Reilly Jr JJ et al. Inorg Chem, 1968, 7: 2254–2256) first successfully prepared Mg by smelting in 1968. 2 Ni alloy, and reported its corresponding hydride Mg for the first time 2 NeA 4 The crystal structure and hydrogen storage properties of Mg 2 Ni can easily react with H at 2MPa and 300℃. 2 The reaction generates its hydride Mg 2 NeA 4 The hydride dehydrogenation enthalpy change is about 64 kJ / mol -1 , purer magnesium (75kJ / mol -1), but its 3.6wt.% hydrogen capacity is reduced compared with pure magnesium. Yu et al. (Yanchong Yu et al. International Journal of Hydrogen Energy, 2022, 47(63): 27059-27070.) prepared Mg-Ni-Y alloy by vacuum induction melting, in which the Mg80Ni15Y5 sample can completely release hydrogen within 5 minutes at 320°C. The alloy based on the ternary magnesium alloy system composed of transition metals and rare earth metals can form a long-period phase well. The nanoparticles decomposed into the long-period phase after the first activation can provide more active sites for the reaction, provide more active sites and diffusion channels for the dissociation and transfer of hydrogen, and achieve better hydrogen storage performance.
[0004] Catalyst modification is an effective way to improve the hydrogen absorption and desorption performance of magnesium-based hydrogen storage systems. Cui (Cui Jet al. J Mater Chem A 2013; 1: 5603-11.) coated different Ti-based nano-scale catalysts on the surface of ball-milled Mg powder. After treatment, the hydrogen release rate reached 5wt.% within 15min at 250℃. Ouyang (Ouyang LZ et al. J Phys Chem C 2014; 118: 7808-20.) synthesized CeH 2.73 The Mg-based composite material with Ni catalyst absorbs hydrogen at room temperature and releases hydrogen at 232°C, with a capacity of up to 4wt.%. The addition of a small amount of catalyst can not only maintain a high hydrogen storage capacity, but also effectively improve its hydrogen storage kinetics and cycle stability.
[0005] At present, the production of magnesium powder in my country generally adopts mechanical crushing method, which is realized by lathe, milling, planing, grinding and other equipment. The milling machine is used to make chips, and the magnesium chips are put into the high-speed eddy current magnesium powder machine (speed of 3800r / min). A strong eddy current effect occurs in the machine body. The magnesium chips constantly collide with each other in the strong eddy current effect, and the edges and corners are ground off to form powder. However, most of the powders produced in this way are rhombus or other irregular shapes, and the particle size is only 20-150 meshes. The activity and bulk density are low, and it pollutes the environment during production, so it is not very safe. The atomization method is also called the spray method. It is a method of directly crushing liquid metal or alloy to obtain powder. Compared with the mechanical crushing method, the mechanical crushing method destroys the bond between solid metal atoms by mechanical action, while the atomization method can disperse it into droplets as long as it overcomes the bonding force between liquid metal atoms. Therefore, the external force required for the atomization process is much smaller than that of mechanical crushing. Therefore, in terms of energy consumption, the atomization method is a simple and economical method for producing metal powder. Therefore, the atomization method can be used as a preparation method for new magnesium-based hydrogen storage materials to make up for the shortcomings of existing magnesium-based hydrogen storage materials.
[0006] Although the catalysts reported so far have improved the performance of magnesium-based hydrogen storage materials to varying degrees, they are generally difficult to activate and have high costs and poor practicality, which hinders their further promotion and development. The development of efficient and low-cost magnesium-based hydrogen storage material catalysts and preparation methods has important development prospects and practical value. Summary of the invention
[0007] The present invention provides an atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase and a preparation method thereof. The hydrogen storage composite material can be put into use after being activated once or twice at 300°C, has a low initial hydrogen absorption and desorption temperature (the initial hydrogen absorption temperature is room temperature), can maintain a relatively fast hydrogen absorption and desorption speed, has good cycle stability and a relatively high hydrogen storage capacity, has a simple preparation process and is suitable for large-scale production, and has a good development prospect and practical application value.
[0008] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0009] The invention discloses an atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase, wherein the hydrogen storage composite material is formed by mixing a magnesium-based hydrogen storage alloy obtained by an atomization method and a rare earth titanium complex phase.
[0010] Furthermore, in the hydrogen storage composite material, the mass ratio of the magnesium-based hydrogen storage alloy to the rare earth titanium composite phase is 80%-95%:20%-5%.
[0011] Furthermore, the rare earth titanium complex phase is formed by mixing nano-Ti powder and rare earth metal. The rare earth metal in the rare earth titanium complex phase is at least one of La, Ce and Y. The particle size of the nano-Ti powder is between 30 and 100 nm. In the rare earth titanium complex phase, the mass ratio of rare earth metal to nano-Ti powder is 1:1 to 5. The preparation method of the rare earth titanium complex phase is: the rare earth metal and nano-Ti powder are mixed uniformly by mechanical dry ball milling to obtain the rare earth titanium complex phase, and the conditions of the mechanical dry ball milling are: in an inert gas (argon and / or helium) atmosphere, the ball-to-material ratio is 10 to 50:1 (preferably 20:1), the ball milling speed is 100 to 600 rpm (preferably 300 rpm), and the ball milling time is 0.5 to 6 hours (preferably 1 hour).
[0012] Furthermore, the magnesium-based hydrogen storage alloy is selected from one of the Mg-Ni-RE alloys, and the mass percentage of magnesium in the Mg-Ni-RE is not less than 80%. RE in the Mg-Ni-RE alloy is a rare earth metal element, including one of Y, Ce and La. The method for preparing the magnesium-based hydrogen storage alloy by atomization is: after removing impurities from the surface of pure magnesium ingots, Mg-Ni intermediates, and Mg-Re intermediate alloys, they are smelted using vacuum smelting equipment, and then the resulting smelting liquid is centrifugally atomized, and the resulting atomized droplets are cooled into powder, which is then collected and sieved to obtain a spherical magnesium-based hydrogen storage alloy that can pass through a 150-mesh sieve.
[0013] Furthermore, the magnesium-based hydrogen storage alloy and the rare earth titanium complex phase are mixed uniformly by mechanical dry ball milling to obtain an atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase, wherein the conditions for the mechanical dry ball milling are: carried out under an inert gas (argon and / or helium) atmosphere, the ball-to-material ratio is 10 to 50:1 (preferably 20:1), the ball milling speed is 100 to 600 rpm (preferably 300 rpm), and the ball milling time is 6 to 60 h (preferably 48 h).
[0014] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0015] The hydrogen storage composite material provided by the present invention introduces RE-Ti complex phase into the atomized magnesium-based hydrogen storage alloy Mg-Ni-RE for catalysis, which gives the material excellent activity and significant advantages in hydrogen absorption and desorption kinetics, effectively reduces the starting temperature threshold of hydrogen absorption and desorption, enables it to absorb hydrogen at near room temperature, and broadens the application scenarios of hydrogen storage materials. The specific beneficial effects are reflected in:
[0016] (1) The alloy powder prepared by atomization technology has a small and uniform particle size, regular particle shape, and a high spherical rate;
[0017] (2) The Mg-Ni-RE alloy has a high content of active magnesium. After a simple ball milling treatment with the RE-Ti composite phase, the activation process can be completed through only 1 to 2 cycles of hydrogen absorption and desorption at 300°C, which significantly reduces the activation energy consumption and time of the material, showing good activation efficiency and stability.
[0018] (3) It has a lower hydrogen absorption and desorption temperature, and the hydrogen absorption and desorption rate is significantly improved, which greatly improves the hydrogen storage efficiency and kinetic performance of the material.
[0019] (4) While maintaining a rapid rate of hydrogen absorption and desorption, its cycle stability is also excellent, providing a solid guarantee for long-term and reliable application.
[0020] (5) In addition, the preparation process of the present invention is simple, efficient and easy to control. The prepared magnesium-based hydrogen storage composite material has high batch consistency and the production technology is relatively mature, which provides the possibility for large-scale and batch production and meets the urgent needs of modern industry for efficient, economical and high-density solid-state hydrogen storage materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the preparation of atomized magnesium-based hydrogen storage materials containing rare earth titanium composite phase;
[0022] Figure 2 is a SEM image of the Mg-Ni-Y alloy prepared in Example 1;
[0023] Figure 3 This is the SEM image of Mg-Ni-Y+La-Ti prepared in Example 1;
[0024] Figure 4 XRD pattern of the Mg-Ni-Y alloy prepared in Example 1;
[0025] Figure 5 XRD pattern of Mg-Ni-Y+La-Ti prepared in Example 1;
[0026] Figure 6 The SEM image of Mg-Ni-Y+La-Ti prepared in Example 1 is compared with 1;
[0027] Figure 7 The SEM image of Mg-Ni-Y+La-Ti prepared in Example 1 is compared with that of Example 2;
[0028] Figure 8 This is a kinetic hydrogen absorption curve of Mg-Ni-Y+La-Ti prepared in Example 1;
[0029] Fig. 9 The kinetic hydrogen release curve of Mg-Ni-Y+La-Ti prepared in Example 1;
[0030] Fig.10 This is the PCT hydrogen absorption and desorption curve of Mg-Ni-Y+La-Ti prepared in Example 1.
[0031] Fig.11 is an isothermal hydrogen release curve of Mg-Ni-Y+La-Ti prepared in Example 1;
[0032] Fig.12 is a graph showing the isothermal hydrogen absorption of Mg-Ni-Y+La-Ti prepared in Example 1;
[0033] Fig.13 The four activation hydrogen absorption curves of Mg-Ni-Y+La-Ti prepared in Example 1;
[0034] Fig.14 This is the SEM image of Mg-Ni-La+Ce-Ti prepared in Example 5;
[0035] Fig.15 This is a kinetic hydrogen absorption curve diagram of Mg-Ni-La+Ce-Ti prepared in Example 5;
[0036] Fig.16 This is a kinetic hydrogen release curve of Mg-Ni-La+Ce-Ti prepared in Example 5;
[0037] Fig.17 This is the PCT hydrogen absorption and desorption curve of Mg-Ni-La+Ce-Ti prepared in Example 5.
[0038] Fig.18 The four activation hydrogen absorption curves of Mg-Ni-La+Ce-Ti prepared in Example 5;
[0039] Fig.19 This is the SEM image of Mg-Ni-Ce+Y-Ti prepared in Example 9;
[0040] Fig. 20 This is a kinetic hydrogen absorption curve diagram of Mg-Ni-Ce+Y-Ti prepared in Example 9;
[0041] Fig.21 This is a kinetic hydrogen release curve of Mg-Ni-Ce+Y-Ti prepared in Example 9;
[0042] Fig. 22 This is the PCT hydrogen absorption and desorption curve of Mg-Ni-Ce+Y-Ti prepared in Example 9.
[0043] Fig.23 The four activation hydrogen absorption curves of Mg-Ni-Ce+Y-Ti prepared in Example 9;
[0044] Fig.24 The kinetic hydrogen absorption curve of the atomized Mg-Ni-Y prepared in Comparative Example 1;
[0045] Fig.25 The kinetic hydrogen release curve of atomized Mg-Ni-Y prepared in Comparative Example 1;
[0046] Fig.26 This is the hydrogen absorption curve of the molten Mg-Ni-Y prepared in Comparative Example 2 after four activations. DETAILED DESCRIPTION
[0047] The following is a specific example description of the embodiments of the present invention, which is intended to help those skilled in the art better understand the core content and potential advantages of the present invention. The embodiments of the present invention are not limited to these examples, and those skilled in the art can easily understand and apply other advantages and effects of the present invention based on the contents disclosed in this specification. At the same time, the present invention can also be implemented or applied through different embodiments according to specific needs and application scenarios. The various details and parameter settings in this specification can also be appropriately modified or changed according to different viewpoints and application requirements without departing from the basic principles and spirit of the present invention.
[0048] Example 1
[0049] This embodiment provides an atomized Mg-Ni-Y hydrogen storage composite material containing La-Ti composite phase, and the specific preparation method is as follows:
[0050] (1) In an argon-protected glove box, 0.125 g of La powder and 0.125 g of Ti powder were weighed and mixed in a mass ratio of 1:1, and placed in a zirconia ball mill for mechanical dry ball milling to obtain La-Ti composite phase. Ball milling conditions: ball-to-material ratio of 20:1; ball milling speed of 300 rpm; ball milling time of 1 h (forward rotation for 10 min, stop for 5 min, then reverse rotation for 10 min, stop for 5 min, 30 min as one cycle), the lining material of the ball mill and the ball milling material are both zirconia, and the ball milling ball diameters are 8 mm and 6 mm.
[0051] (2) Preparation of atomized Mg-Ni-Y alloy: First, the pure magnesium ingot, Mg-30% Ni, and Mg-30% Y master alloys are thoroughly surface-cleaned to ensure the purity of the raw materials. Then, the raw materials after impurities removal are melted using a magnetic levitation vacuum melting equipment at a mass ratio of 94:4:2 among the pure magnesium ingot, Mg-30% Ni, and Mg-30% Y master alloy to obtain a uniform molten liquid. When the molten liquid is in a stable state, the obtained molten liquid is centrifugally atomized, and the obtained atomized droplets are cooled into powder, which is then collected and passed through a 150-mesh sieve to obtain a spherical Mg-Ni-Y alloy.
[0052] (3) Take the spherical Mg-Ni-Y alloy and mix it with the La-Ti complex phase in an argon protection glove box and put it into a ball mill. The mass ratio of Mg-Ni-Y alloy to La-Ti complex phase is 95%:5%. The atomized Mg-Ni-Y hydrogen storage composite material containing La-Ti complex phase (referred to as Mg-Ni-Y+La-Ti) is prepared by mechanical dry ball milling. Ball milling conditions: ball-to-material ratio 20:1, ball milling speed 300rpm, ball milling time 48h (forward rotation 10min stop 5min, then reverse rotation 10min stop 5min, 30min as a cycle), the ball mill liner material and ball milling ball material are both zirconia, and the ball milling ball diameters are 8mm and 6mm.
[0053] Figure 2 The scanning electron microscope (SEM) image of the Mg-Ni-Y alloy prepared in step (2) of this embodiment is shown. It can be clearly seen from the figure that the Mg-Ni-Y alloy particles obtained by the atomization technology are regular spherical, and the particle size is mainly distributed around 100 μm.
[0054] Figure 3 The scanning electron microscope (SEM) image of Mg-Ni-Y+La-Ti prepared in step (3) of this embodiment is shown. It can be clearly observed from the figure that the particle size of the Mg-Ni-Y alloy after ball milling is significantly refined, and the size is reduced to 5-40μm. The surface defects are significantly increased, and La-Ti particles are attached to the surface.
[0055] Figure 4 The X-ray diffraction (XRD) spectrum of the Mg-Ni-Y alloy prepared in step (2) of this embodiment is shown. From the analysis of the spectrum, it can be seen that the Mg-Ni-Y alloy is mainly composed of α-Mg phase and Mg2Ni phase.
[0056] Figure 5 The X-ray diffraction (XRD) pattern of Mg-Ni-Y+La-Ti prepared in step (3) of this embodiment is shown. Analysis of the pattern shows that in addition to the α-Mg phase and the Mg2Ni phase, there are also Ti and La phases.
[0057] For comparison, a Mg-Ni-Y+La-Ti comparison sample is also prepared in this embodiment. The preparation method is the same as that of the Mg-Ni-Y+La-Ti sample, with the only difference being that the ball-to-material ratio in steps (1) and (3) is changed to 10:1 (denoted as Mg-Ni-Y+La-Ti comparison 1) or 30:1 (denoted as Mg-Ni-Y+La-Ti comparison 2).
[0058] Figure 6 The scanning electron microscope (SEM) image of Mg-Ni-Y+La-Ti comparison 1 is shown. It can be clearly seen from the figure that when the ball-to-material ratio is 10:1, the particle size is mainly distributed around 80μm. Figure 7 The scanning electron microscope (SEM) image of Mg-Ni-Y+La-Ti vs. 2 is shown. It is clear from the figure that when the ball-to-material ratio is 30:1, the particle size is mainly distributed around 90μm. It can be concluded that the change of the ball-to-material ratio will greatly affect the particle size, thereby affecting the hydrogen storage performance of the material.
[0059] 100 mg of the hydrogen storage composite material prepared in this example was weighed and placed in a PCT testing instrument, and its hydrogen storage performance was tested under the following conditions:
[0060] 1. At 20-400℃, test the kinetic hydrogen absorption curve of the sample under 3-3.5MPa hydrogen pressure (the results are as follows Figure 8 As shown), and the kinetic hydrogen release curve under 0.01MPa hydrogen pressure (results as shown Fig. 9 shown).
[0061] It can be clearly observed from the figure that the initial hydrogen absorption temperature of the hydrogen storage composite material prepared in this embodiment is 20°C, and the initial hydrogen release temperature is 229°C.
[0062] 2. PCT curve of the test sample.
[0063] Fig.10 The PCT curve of the hydrogen storage composite material prepared in this embodiment is shown. It can be clearly seen from the figure that the total amount of hydrogen absorption of Mg-Ni-Y+La-Ti prepared in this embodiment reaches 6.68%wt.%, and the total amount of hydrogen release reaches 6.66%wt.%, which is very close to the ideal hydrogen absorption and release amount of this hydrogen storage composite material.
[0064] 3. At 300°C, the isothermal hydrogen absorption curve of the test sample under a hydrogen pressure of 3-3.5MPa, and the isothermal hydrogen desorption curve under a hydrogen pressure of 0.01MPa.
[0065] Fig.11 2 is the isothermal hydrogen release curve. It can be clearly seen from the figure that the Mg-Ni-Y+La-Ti prepared in this embodiment releases more than 1.5 wt.% of hydrogen within 10 minutes at 300°C.
[0066] Fig.12 2 is the isothermal hydrogen absorption curve obtained. It can be clearly seen from the figure that the Mg-Ni-Y+La-Ti prepared in this embodiment can absorb more than 2.5wt.% of hydrogen within 10 minutes at 300°C.
[0067] It can be seen that the hydrogen storage composite material prepared in this embodiment not only has a lower initial hydrogen desorption temperature, but also has significantly improved hydrogen desorption kinetics and hydrogen absorption kinetics.
[0068] 4. Test the hydrogen absorption and desorption activation curve of the sample at 300℃ under 3-3.5MPa hydrogen pressure.
[0069] Fig.13This is the activation curve of the hydrogen storage composite material prepared in this embodiment. As can be seen from the figure, compared with the magnesium-based material prepared by the traditional high-temperature melting method, which requires at least six cycles of hydrogen absorption and desorption activation at 400°C to achieve good performance, the hydrogen storage composite material prepared in this embodiment only requires one cycle of hydrogen absorption and desorption activation at 300°C to show excellent performance. This significant performance improvement means that the activation time of the material has been greatly improved, providing a more convenient and efficient solution for the practical application of magnesium-based hydrogen storage materials.
[0070] Example 2
[0071] In this example, an atomized Mg-Ni-Ce hydrogen storage composite material containing a La-Ti complex phase (denoted as Mg-Ni-Ce+La-Ti) is prepared in the same manner as in Example 1, with the only difference being that the Mg-30% Y master alloy in step (2) is replaced by an equal amount of Mg-30% Ce master alloy.
[0072] Example 3
[0073] In this example, an atomized Mg-Ni-La hydrogen storage composite material containing a La-Ti complex phase (denoted as Mg-Ni-La+La-Ti) is prepared by the same method as in Example 1, with the only difference being that the Mg-30% Y master alloy in step (2) is replaced by an equal amount of Mg-30% La master alloy.
[0074] Example 4
[0075] In this example, an atomized Mg-Ni-Y hydrogen storage composite material containing a Ce-Ti complex phase (denoted as Mg-Ni-Y+Ce-Ti) was prepared in the same manner as in Example 1, with the only difference being that the La powder in step (1) was replaced with an equal amount of Ce powder.
[0076] Example 5
[0077] In this example, an atomized Mg-Ni-La hydrogen storage composite material containing a Ce-Ti complex phase (denoted as Mg-Ni-La+Ce-Ti) is prepared by the same method as in Example 1, with the only difference being that the La powder in step (1) is replaced by an equal amount of Ce powder and the Mg-30% Y master alloy in step (2) is replaced by an equal amount of Mg-30% La master alloy.
[0078] Fig.14 The scanning electron microscope (SEM) image of Mg-Ni-La+Ce-Ti prepared in Example 5 is shown. It can be observed from the figure that the particle size of the Mg-Ni-La alloy after ball milling is significantly refined and reduced to 20-40 μm. The surface defects are significantly increased, and Ce-Ti particles are attached to the surface.
[0079] Fig.15and Fig.16 This is the kinetic hydrogen absorption and desorption curve of Mg-Ni-La+Ce-Ti prepared in Example 5. It can be clearly observed from the figure that the initial hydrogen absorption temperature of the material is 28°C and the initial hydrogen desorption temperature is 268°C.
[0080] Fig.17 The PCT curve of the hydrogen storage composite material prepared in this embodiment is shown. It can be clearly seen from the figure that the total amount of hydrogen absorption of Mg-Ni-La+Ce-Ti prepared in this embodiment reaches 6.74%wt.%, and the total amount of hydrogen release reaches 6.7%wt.%, which is very close to the ideal hydrogen absorption and release amount of this hydrogen storage composite material.
[0081] Fig.18 The activation curve of Mg-Ni-La+Ce-Ti prepared in Example 5 is shown. As can be seen from the figure, the material only needs two cycles of hydrogen absorption and desorption activation at 300°C to show excellent performance.
[0082] Example 6
[0083] In this example, an atomized Mg-Ni-Ce hydrogen storage composite material containing a Ce-Ti complex phase (referred to as Mg-Ni-Ce+Ce-Ti) was prepared in the same manner as in Example 1, except that the La powder in step (1) was replaced with an equal amount of Ce powder and the Mg-30%Y master alloy in step (2) was replaced with an equal amount of Mg-30%Ce master alloy.
[0084] Example 7
[0085] In this example, an atomized Mg-Ni-La hydrogen storage composite material containing a Y-Ti complex phase (denoted as Mg-Ni-La+Y-Ti) is prepared by the same method as in Example 1, with the only difference being that the La powder in step (1) is replaced by an equal amount of Y powder and the Mg-30% Y master alloy in step (2) is replaced by an equal amount of Mg-30% La master alloy.
[0086] Example 8
[0087] In this example, an atomized Mg-Ni-Y hydrogen storage composite material containing a Y-Ti complex phase (denoted as Mg-Ni-Y+Y-Ti) was prepared in the same manner as in Example 1, with the only difference being that the La powder in step (1) was replaced with an equal amount of Y powder.
[0088] Example 9
[0089] In this example, an atomized Mg-Ni-Ce hydrogen storage composite material containing a Y-Ti complex phase (denoted as Mg-Ni-Ce+Y-Ti) is prepared by the same method as in Example 1, with the only difference being that the La powder in step (1) is replaced by an equal amount of Y powder and the Mg-30% Y master alloy in step (2) is replaced by an equal amount of Mg-30% Ce master alloy.
[0090] Fig.19 The scanning electron microscope (SEM) image of Mg-Ni-Ce+Y-Ti prepared in Example 9 is shown. It can be observed from the figure that the particle size of the Mg-Ni-Ce alloy after ball milling is significantly refined and reduced to 20-45 μm. The surface defects are significantly increased, and the Y-Ti particles are attached to the surface.
[0091] Fig. 20 and Fig.21 This is the kinetic hydrogen absorption and desorption curve of Mg-Ni-Ce+Y-Ti prepared in Example 9. It can be clearly observed from the figure that the initial hydrogen absorption temperature of the material is 23°C, and the initial hydrogen desorption temperature is 249°C.
[0092] Fig. 22 The PCT curve of the hydrogen storage composite material prepared in this embodiment is shown. It can be clearly seen from the figure that the total amount of hydrogen absorption of Mg-Ni-La+Ce-Ti prepared in this embodiment reaches 6.71%wt.%, and the total amount of hydrogen release reaches 6.69%wt.%, which is very close to the ideal hydrogen absorption and release amount of this hydrogen storage composite material.
[0093] Fig.23 The activation curve of Mg-Ni-Ce+Y-Ti prepared in Example 9 is shown. As can be seen from the figure, the material only needs two cycles of hydrogen absorption and desorption activation at 300°C to show excellent performance.
[0094] Comparative Example 1
[0095] This comparative example provides an atomized Mg-Ni-Y hydrogen storage alloy, and the specific preparation method is as follows:
[0096] First, the pure magnesium ingot, Mg-30% Ni, and Mg-30% Y master alloys are thoroughly surface-cleaned to ensure the purity of the raw materials. Then, the raw materials after impurities removal are melted using a magnetic levitation vacuum melting equipment at a mass ratio of 94:4:2 among the pure magnesium ingot, Mg-30% Ni, and Mg-30% Y master alloy to obtain a uniform molten liquid. When the molten liquid is in a stable state, the obtained molten liquid is centrifugally atomized, and the obtained atomized droplets are cooled into powder, which is then collected and passed through a 150-mesh sieve to obtain a spherical atomized Mg-Ni-Y alloy.
[0097] Fig.24 and Fig.25 The kinetic hydrogen absorption and desorption curve of the Mg-Ni-Y hydrogen storage alloy prepared in Comparative Example 1. It can be clearly observed from the figure that the initial hydrogen absorption temperature of the material is 58°C, and the initial hydrogen desorption temperature is 293°C.
[0098] Comparative Example 2
[0099] This embodiment provides a molten Mg-Ni-Y hydrogen storage alloy, and the specific preparation method is as follows:
[0100] (1) Using pure Mg, Y, and Ni ingots with a purity of not less than 99.5% as raw materials, Mg-Ni-Y alloy (mass ratio of 94:4:2) was prepared by vacuum induction furnace method. During the smelting process, the alloy was heated by medium frequency power supply and induction coil, and argon gas with a purity of 99.999% was pumped into the furnace to prevent the alloy from oxidation. After smelting, the molten alloy was poured into a copper mold to prepare an ingot. The ingot was then mechanically crushed, and the particle size of the crushed alloy powder was about 150μm.
[0101] (2) The crushed alloy powder was placed in a ball mill in an argon-protected glove box, and Mg-Ni-Y hydrogen storage alloy was prepared by mechanical dry ball milling. Ball milling conditions: ball-to-material ratio 20:1, ball milling speed 300 rpm, ball milling time 48 h (forward rotation 10 min, stop 5 min, reverse rotation 10 min, stop 5 min, 30 min as a cycle), ball mill liner material and ball milling ball material are both zirconia, ball milling ball diameters are 8 mm and 6 mm.
[0102] Fig.26 The activation curve of the molten Mg-Ni-Y hydrogen storage alloy prepared in Comparative Example 2 is shown. As can be seen from the figure, compared with the magnesium-based composite hydrogen storage material prepared in Example 1, which only needs one hydrogen absorption and desorption cycle activation at 300°C to achieve good performance, the Mg-Ni-Y hydrogen storage alloy prepared in this example needs six hydrogen absorption and desorption cycle activations at 400°C to achieve good performance.
[0103] Table 1 Comparison of the performance of hydrogen storage composite materials prepared in Examples 1 to 9
[0104]
[0105] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase, characterized in that: The hydrogen storage composite material is formed by mixing a magnesium-based hydrogen storage alloy prepared by an atomization method with a rare earth titanium complex phase; the rare earth titanium complex phase is formed by mixing nano-Ti powder with a rare earth metal.
2. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: In the hydrogen storage composite material, the mass ratio of the magnesium-based hydrogen storage alloy to the rare earth titanium composite phase is 80%-95%:20%-5%.
3. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: The rare earth metal in the rare earth titanium composite phase is at least one of La, Ce and Y.
4. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: In the rare earth titanium composite phase, the mass ratio of rare earth metal to nano-Ti powder is 1:1-5.
5. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: The particle size of the nano-Ti powder is between 30 and 100 nm.
6. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: The preparation method of the rare earth titanium complex phase is: rare earth metal and nano-Ti powder are mixed uniformly by mechanical dry ball milling to obtain the rare earth titanium complex phase. The conditions of the mechanical dry ball milling are: carried out under an inert gas atmosphere, the ball-to-material ratio is 10-50:1, the ball milling speed is 100-600rpm, and the ball milling time is 0.5-6h.
7. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 1, characterized in that: The magnesium-based hydrogen storage alloy is selected from one of Mg-Ni-RE alloys, and the mass percentage of magnesium in the Mg-Ni-RE is not less than 80%.
8. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 7, characterized in that: In the Mg-Ni-RE alloy, RE is a rare earth metal element, including one of Y, Ce and La.
9. The atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to claim 7 or 8, characterized in that: The method for preparing magnesium-based hydrogen storage alloy by atomization is as follows: after removing impurities from the surface of pure magnesium ingots, Mg-Ni intermediate and Mg-Re intermediate alloys, they are smelted using vacuum melting equipment, and then the resulting smelting liquid is centrifugally atomized. After the resulting atomized droplets are cooled into powder, they are collected and sieved to obtain spherical magnesium-based hydrogen storage alloys that can pass through a 150-mesh sieve.
10. A method for preparing the atomized magnesium-based hydrogen storage composite material containing rare earth titanium complex phase according to any one of claims 1 to 9, characterized in that: The magnesium-based hydrogen storage alloy and the rare earth titanium complex phase are mixed uniformly by mechanical dry ball milling to obtain an atomized magnesium-based hydrogen storage composite material containing a rare earth titanium complex phase, wherein the mechanical dry ball milling conditions are: carried out under an inert gas atmosphere, a ball-to-material ratio of 10 to 50:1, a ball milling speed of 100 to 600 rpm, and a ball milling time of 6 to 60 hours.
Citation Information
Patent Citations
Nano-catalysis complex nitride hydrogen storing material and method for preparing the same
CN101293630A
Mg-Ti-RE-Ni-based hydrogen-storage alloy and preparation method thereof
CN104593651A
Magnesium-based nano-composite hydrogen storage material with dispersively distributed catalytic phase and preparation method of material
CN107345282A
Magnesium-based amorphous alloy hydrogen storage material cooperatively modified by nano TiF3 and TiO2 nanotubes and preparation method thereof
CN113667908A
Magnesium-based hydrogen storage alloy block and preparation method thereof
CN114507798A